OP0304 Multidisciplinary collaboration among young specialists: results of an ongoing international survey by young organisations. (12th June 2018) - Kostine, M.; Najm, A.; Pauling, J.; Ferreira, A.C.; Stevens, K.; Smith, E.; Eguiluz Gracia, I.; Ramiro, S.; Nikiphorou, E.; Molto, A.; Alunno, A.; Studenic, P.; et al.
Abstract : Background: Young clinicians and researchers frequently work alongside other medical specialists in order to share expertise, knowledge and skills. Multidisciplinary work is worthwhile but may be sometimes challenging. Objectives: To describe current clinical and research collaboration among young specialists and to identify some perspectives to develop such collaborations. Methods: An online survey was disseminated by email and social media (facebook and twitter) to members of the Emerging European League Against Rheumatism Network (EMEUNET), the Young Nephrologists' Platform (YNP), the Paediatric Rheumatology European Society Emerging Rheumatologists and Researchers (PReS EMERGE), and the European Academy of Allergy and Clinical Immunology Junior Members (EAACI JM). Results: Of 354 respondents from 40 countries, 60% were female, 23% were aged below 30 years and 67% 31–40 years. Young rheumatologists were the most represented (36%), followed by young nephrologists (24%), young paediatricians (18%), young allergologists (11%) then young internists (3%) and several other specialties (as clinical immunology, dermatology, pulmonology, orthopaedics). 60% were certified specialists, 34% in training and 6% were researchers without clinical work. Overall, the top 3 specialties for clinical collaboration in daily practice were radiology, cardiology and dermatology. Collaborations were reported frequently by phone and email, also by various combined clinics while common local multidisciplinary meetings were uncommon. Of note, 71% of respondents found collaboration with young colleagues easier than with senior specialists. Research collaboration usually started by knowing other specialists (73%) and/or by attending common meetings (39%). 96% would like to develop clinical research collaborations and 69% basic research collaborations. The majority of young specialists would be interested in online (84%) and/or 1–2 days (86%) common courses including cases discussion (80%) and training workshops (84%), as well as webinars recorded with several specialists on a specific disease (96%). Respondents were a bit less enthusiastic with developing collaboration through social media (facebook 61%, twitter 58%) but interested in common apps (71%). Conclusions: This collaborative initiative highlighted wishes from young specialists for developing 1) regular local multidisciplinary meetings to discuss complex patients 2) clinical research collaboration with combined grants and 3) multidisciplinary online projects such as common courses, webinars and apps. Acknowledgements: We thank all members of young organisations for their active participation. Disclosure of Interest: None declared